2022
DOI: 10.1111/jnc.15733
|View full text |Cite
|
Sign up to set email alerts
|

Leptin‐based hexamers facilitate memory and prevent amyloid‐driven AMPA receptor internalisation and neuronal degeneration

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…In conclusion, it is well established that leptin has potent neuroprotective properties against the aberrant effects of Aβ (Doherty et al, 2013, 2022; Magalhães et al, 2015; Malekizadeh et al, 2017; McGregor & Harvey, 2018). Recent studies have highlighted the pivotal role of tau in mediating Aβ‐induced toxicity and have also identified the crucial role tau plays in AD‐related synaptic dysfunction.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…In conclusion, it is well established that leptin has potent neuroprotective properties against the aberrant effects of Aβ (Doherty et al, 2013, 2022; Magalhães et al, 2015; Malekizadeh et al, 2017; McGregor & Harvey, 2018). Recent studies have highlighted the pivotal role of tau in mediating Aβ‐induced toxicity and have also identified the crucial role tau plays in AD‐related synaptic dysfunction.…”
Section: Discussionmentioning
confidence: 83%
“…Previous studies have shown that movement of tau to synapses results in AMPAR removal from hippocampal synapses (Miller et al, 2014; Teravskis et al, 2021). To verify if Aβ 1‐42 promotes removal of synaptic AMPARs, immunocytochemical approaches were used to monitor the cell surface expression of the AMPA receptor subunit, GluA1 (Doherty et al, 2022; Moult et al, 2010). Incubation with Aβ 1‐42 , (1 μM, 1 h) had no effect on GluA1 surface expression per se as surface GluA1 immunolabelling was not significantly different to control (0.90 ± 0.02; n = 48 dendrites; n = 4 cultures; F [7376] = 13.4; p = 0.14; Figure 5a,b).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations